If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6y + -22 = y + -1 Reorder the terms: -22 + 6y = y + -1 Reorder the terms: -22 + 6y = -1 + y Solving -22 + 6y = -1 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. -22 + 6y + -1y = -1 + y + -1y Combine like terms: 6y + -1y = 5y -22 + 5y = -1 + y + -1y Combine like terms: y + -1y = 0 -22 + 5y = -1 + 0 -22 + 5y = -1 Add '22' to each side of the equation. -22 + 22 + 5y = -1 + 22 Combine like terms: -22 + 22 = 0 0 + 5y = -1 + 22 5y = -1 + 22 Combine like terms: -1 + 22 = 21 5y = 21 Divide each side by '5'. y = 4.2 Simplifying y = 4.2
| X=2-2(-2) | | 42-2*6=5*6 | | y=3x^2-24x+144 | | 4(x-4)=7x-34 | | 72=12(-3x) | | 5(5.4)-4=31 | | -9x-36=11x+24 | | (-5.2)=0.04m | | 0.002+0.04=2.04 | | 0=14t+28 | | (-5.2)=0.04 | | 4c=-18 | | -8x-70=2x+160 | | 20=y-2.1 | | 2x=4y+2z | | 4x+2.5x=39 | | -4+x-3=24 | | 8x^2-24x=14 | | -31-11x=11-9x | | 8m+4=m | | 4r-7=8t+13 | | -74=-110+6x | | 14+6=2(5+7v)-4 | | 10n+5=5n+25 | | 5x-126=135-4x | | 9x-(x+22)=3x+3 | | 9x+10-5x=-12 | | 4+4b-3b=2+3b | | 3x+13=5x-3 | | 16-4=3(2-x) | | 7x+-7=12x+13 | | -3x+7y+14=0 |